2014
DOI: 10.1021/jo501041b
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Conjugated Hydroporphyrin Dyads: Extensive Modification of Hydroporphyrins’ Properties by Expanding the Conjugated System

Abstract: We report the synthesis and basic photophysical characterization of strongly conjugated hydroporphyrin (chlorin and bacteriochlorin) dyads. Hydroporphyrins are connected at their respective 13 (β) or 15 (meso) positions by ethynyl or butadiynyl linkers. Synthesis entails a series of palladium-catalyzed reactions, starting from appropriate bromobacteriochlorin or bromochlorin. Strong conjugation in the dyads results in a significant bathochromic shift of longest-wavelength (Qy-like) band, which in case of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(92 citation statements)
references
References 91 publications
6
83
3
Order By: Relevance
“…Additional notable chlorin building blocks are shown in Scheme 94. The set includes the following: (1) chlorins with a single halo or ethyne ( 217 , 292 218 , 272 219 , 442 220 , 442 221 , 256 and 222 256 ); (2) oxochlorins with a single halo or ethyne ( 223 , 259 224 258 ); (3) chlorins with two halo or two ethynes ( 225 , 284 226 284 ); (4) chlorins with one halo and one ethyne ( 227 , 284 228 299 ); and (5) a chlorin with two bromo substituents and one ethyne ( 229 278 ).…”
Section: Smorgasbord Of Chlorinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional notable chlorin building blocks are shown in Scheme 94. The set includes the following: (1) chlorins with a single halo or ethyne ( 217 , 292 218 , 272 219 , 442 220 , 442 221 , 256 and 222 256 ); (2) oxochlorins with a single halo or ethyne ( 223 , 259 224 258 ); (3) chlorins with two halo or two ethynes ( 225 , 284 226 284 ); (4) chlorins with one halo and one ethyne ( 227 , 284 228 299 ); and (5) a chlorin with two bromo substituents and one ethyne ( 229 278 ).…”
Section: Smorgasbord Of Chlorinsmentioning
confidence: 99%
“…Chlorin 219 was prepared by reaction of an 8,9-dibromodipyrromethane bearing a 5- p -tolyl group ( 120f-Br 8,9 ; 442 analogue of 120c-Br 8,9 , Scheme 57) with Western half 118 ; subsequent Sonogashira coupling led to ethynylchlorin 220 . Chlorins 221 and 222 were prepared with a suitably diaryl-substituted Eastern half 119-Br 9 /OH and Western half 118 (Scheme 50); oxochlorins 223 and 224 were prepared likewise followed by oxidation of the 17-methylene unit (Scheme 54).…”
Section: Smorgasbord Of Chlorinsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The steric hindrance caused by the methoxy group at the 5-position causes Pd-mediated coupling with the 3,13-dibromobacteriochlorin to proceed regioselectively at the 13-position with one equivalent of the ethyne. 24,35,36 Therefore, the Sonogashira coupling reaction of 3 with methyl 4-ethynylbenzoate ( 4 ) regioselectively proceeded at the 13-position of the macrocycle to give ethynylbacteriochlorin 5 in 42% yield (Scheme 1). Further reaction of 5 with ethyne 6 in the presence of Pd(PPh 3 ) 2 Cl 2 and Et 3 N in DMF at 80 °C gave unsymmetrically substituted bacteriochlorin 7 .…”
Section: Resultsmentioning
confidence: 99%
“…A more pronounced bathochromic shift than observed herein appears to require more extensive modification of the macrocyclic structure. The research reported here predated and somewhat inspired our recent studies on strongly conjugated hydroporphyrin arrays, which appears to be an efficient way to bathochromically shift the chlorin absorption [27]. …”
Section: Resultsmentioning
confidence: 99%